PENGARUH MODEL PEMBELAJARAN CONCEPT SENTENCE TERHADAP KEMAMPUAN MENULIS PUISI KELAS V SD NEGERI 13 TOBOALI - Anjas Fani, Lola; Maulina Hendrik; Agci Hikmawati (JBES (Journal Basic Education Skills), 2023)
This study was motivated by the low ability of students in writing poetry, the students have difficulty expressing ideas and matching the writing the theme appropriately. The purpose of this study was to determine the effect of the Concept Sentence learning model on the ability of fifih-grede students in writing poetry at SD Negeri 13 Toboali. This study used a quantitative approach with the Quasi-Experimental Design method, with Nonequivalent Control Grup Design. The sampling techique used was saturated sampling. Data collection techninques used interviews, tests, and documentation. Data analysis techniques using normality test, homogeneity test, and hypothesis testing used t-test, namely The Polled Variance. Based on the results of the research data analysis obtained by the hypothesis data the value of the tcount is 3.148 an ttable is 2.018. So, it can be concluded that is accepted is rejected. From theses results, it can be concluded that there is an effect of the Concept Sentence learning model on the fifih-grade students’ ability in writing poetry at SD Negeri 13 Toboali.